Effects of humor therapy on fatigue and depression of multiple sclerosis (MS) patients - Moshtagh Eshgh, Zahra; Naghavi, Bahareh; Rashvand, Farnoosh; Alavi Majd, Hamid; Bana Derakhshan, Homayoon (Advances in Nursing & Midwifery, 2011)
Effects of humor therapy on fatigue and depression of multiple sclerosis (MS) patients Moshtagh Eshgh, Z.1* (MSN); Naghavi, B.2 (MS); Rashvand, F.3 (MSN); Alavi Majd, H.4 (PhD), Bana Derakhshan, H. (MSN)5 1. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. *(Corresponding Author) e-mail:z.moshtagh@yahoo.com 2. Lecturer, Dept. of Basic Sciences, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 3. Lecturer, Azad University of Abhar, Abhar, Iran. 4. Associate Professor, Dept. of Biostatistics, Faculty of Paramedical, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 5.Lecturer, Dept. of operating room & Anesthesia, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Abstract Background and aim Multiple sclerosis (MS) is the most common disabling condition in young adults, which is caused by an inflammatory demyelination process in central nervous system. Fatigue and depression are the primary symptoms leading to dysfunction as well as disability in activities of daily living and decreased quality of life. Because of many drug-associated complications, applying other methods to lessen the symptoms seems reasonable. The aim of this study was to determine the effects of humor on fatigue and depression of clients referring to Iranian MS Society. Materials and methods In this one-group before-after clinical trial, 30 MS clients were selected by convenience sampling method. A 4-part questionnaire including demographics, items related to the condition, Fatigue Severity Scale (FSS) and Beck’s Depression Inventory was used for data collection, validated and made reliable by content and test-retest methods respectively. The clients took part in humor therapy sessions 3 times a week, each lasting 30 minutes for 12 weeks. The sessions were hold during the day with entertaining and funny programs recorded on compact discs (CDs). The clients completed the questionnaire before and after the intervention. Data were then analyzed by different statistical methods. Findings A significant decrease was found in mean severities of fatigue and depression after the intervention (P<0.01). Therefore, the hypothesis of the study denoting the effects of humor therapy on severity of fatigue and depression in clients with MS was verified. Conclusion The study revealed that humor therapy may decrease the fatigue and depression of clients with MS. Humor as a simple, low-cost and noninvasive method can be used to overcome many problems of these clients and ultimately lead to decreased fatigue and depression. Keywords: Humor therapy, Fatigue, Depression, Multiple sclerosis (MS) *Corresponding Author: Zahra Moshtagh Eshgh. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: z.moshtagh@yahoo.com